FEM Analysis of a FGM Pre-Stressed Plate Strip With A Circular Hole Under Bending - Yesil, Ulku Babuscu; Atasayanlar, Mehmet Can (TAMKANG UNIV, 2020)
A static analysis of a pre-stressed plate-strip made from functionally-graded material (FGM) containing a circular hole has been investigated under bending forces. The plate-strip is simply supported on two opposite ends and the pre-stresses are formed by the uniformly distributed forces which acts on these two ends before the main loading. The influences of pre-stresses in the plate-strip on the distributions of displacements and stresses around the hole caused by the additional bending forces acting on the upper face-plane of the FGM platestrip are investigated. The Linearized Three-Dimensional Elasticity Theory and the generalized plane-strain conditions are assumed for the modelling of the theoretical investigations. Young's modulus of the medium varies continuously in the horizontal and vertical directions according to power law distribution, but the Poisson's ratio and material density are assumed to be constant. The solution of the considered problem is obtained numerically with the help of the Finite Element Method (FEM). Numerical results of distributions of the displacements and stresses around the hole are presented and discussed for various problem parameters such as, material property, plate size, initial effect and position of the hole.
Keywords: Functionally graded material; Initial stress; Circular hole; Static analysis; FEM; GRADED FINITE-ELEMENTS; STRESS-CONCENTRATION; BEHAVIOR; BEAM; Engineering